Translanguaging as a Practical Theory of Language - Li, Wei (Applied linguistics, 2018)
Abstract This article seeks to develop Translanguaging as a theory of language and discuss the theoretical motivations behind and the added values of the concept. I contextualize Translanguaging in the linguistic realities of the 21st century, especially the fluid and dynamic practices that transcend the boundaries between named languages, language varieties, and language and other semiotic systems. I highlight the contributions Translanguaging as a theoretical concept can make to the debates over the Language and Thought and the Modularity of Mind hypotheses. One particular aspect of multilingual language users’ social interaction that I want to emphasize is its multimodal and multisensory nature. I elaborate on two related concepts: Translanguaging Space and Translanguaging Instinct, to underscore the necessity to bridge the artificial and ideological divides between the so-called sociocultural and the cognitive approaches to Translanguaging practices. In doing so, I respond to some of the criticisms and confusions about the notion of Translanguaging.